Changes of Learning Communication Models in New Normal Adaptation: From Classroom Learning to Distance Learning Environment - Joko S. Dwi Raharjo; Dony Hendartho; Endang Susanti; Retno Ekasari (Yayasan Ilomata, 2021)
Covid-19 pandemic has a significant impact on various aspects of life, both individually, organizationally and nationally. The decision of various countries in the world to do a